A new approach on brewer's spent grains treatment and potential use as lignocellulosic yeast cells carriers - Pires, Eduardo J. (2012)
The major objective of this work is to improve the pretreatments of brewer’s spent grains (BSG) aiming at their use as a source for lignocellulosic yeast carriers (LCYC) production. Therefore, several pretreatments of BSG have been designed aiming at obtaining various yeast carriers, differing on their physicochemical composition. Cellulose, hemicellulose, lignin, fat, protein, and ash content were determined for crude BSG and the LCYCs. The long chain fatty acids profile for the crude BSG was also analyzed. Chemical treatments successfully produced several different LCYC based on BSG. The highest cellulose content in LCYC was achieved upon application of caustic (NaOH) treatment during 40 min. Either caustic or combined acid−caustic treatments predominately generated hydrophobic, negatively charged LCYC. The feasibility of using BSG for LCYC production is strengthened by the fact that added-value byproduct can be extracted before the chemical treatments are applied.